Penyalahgunaan Dana Desa Oleh Kepala Desa di Kabupaten Bangkalan Tahun 2018 - 2023 - Mohammad Rizky Gustiansyah (LPPM Universitas Sains dan Teknologi Komputer, 2023)
Village Chief’s corruption is rife every year, the village head generally uses the village’s funds offered annually by the central government for personal gain, the corruption of village funds byt the village head has a wide range of methods, such as ATM control and the bank book for receipt of funds and a fictious project, the amount of village fund has corrupted from hundreds of millions to billions rupiah, hopefully the corruption in the village will decline which the central government through KPK shoukd act with such force as a “grab hand operation” and coordinate with the relevant parties in order to capture the corrupt.